Implementasi Algoritma Boyer Moore pada Perancangan Aplikasi Kamus Bahasa Inggris Berbasis Web (Studi Kasus: Pondok Pesantren Ishlaahul Ummah) - Hasanatul Athpaliah; Hidayatullah Al Islami (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The process of searching for English words in the Ishlaahul Ummah Islamic Boarding School environment is still done manually by opening each page one by one, a large number of dictionary or book pages, starting from the alphabet A to the alphabet Z. This search process is very useful for anyone who wants to know the meaning every word is in English, but the search process is slow and time-consuming. To speed up and simplify the search process, we need an algorithm that can maximize the search process. In this study, the Boyer-Moore algorithm was applied in designing a web-based English dictionary application using a system development model, namely the waterfall model. The result of this study is a web-based English dictionary application that makes searching for English words faster and more efficient. This is evidenced by the results of an interview with an application user, where previously it took 2 minutes to search for an English word to 30 seconds using this search system that has been built.